A review on life cycle cost analysis of buildings based on building information modeling - Lu, Kun; Deng, Xueyuan; Jiang, Xiaoyan; Cheng, Baoquan; Tam, Vivian W. Y. (Journal of Civil Engineering and Management, 2023)
Life cycle cost analysis (LCCA) plays an essential role in the economic sustainability assessment of buildings, and building information modeling (BIM) offers a potentially valuable approach to fulfilling its requirement. However, the state of LCCA based on BIM is unclear despite previously published works. Therefore, this paper aims to address this gap by reviewing 45 relevant peer-reviewed articles through a systematic literature search, selection, and assessment. The results show that three data exchange methods integrate BIM and LCCA through data input, calculation, and output. Precision management, optimization measures, and parameter analysis through BIM significantly improve the value of buildings. Also, a methodological framework is summarized that combines LCC with other indicators based on BIM to consider economic, environmental, and social impacts, which can be monetized to assess life cycle sustainability costs. These findings provide insights for scholars and practitioners.